One soul at a time : the story of Billy Graham - Wacker, Grant, 1945- (Secunderabad : Grand Rapids, Michigan : GS books, William B. Eerdmans Publishing Company, 2021)
"This compact narrative biography of Billy Graham shows how Graham--more than any other individual--helped create and shape the powerful post-World War II evangelical movement in the United States and in many other parts of the world"--
Includes bibliographical references (pages 301-308) and index
Keywords: Graham, Billy, -- 1918-2018; Evangelists -- United States -- Biography